Rhodium‐Catalyzed Ketone Methylation Using Methanol Under Mild Conditions: Formation of α‐Branched Products1. (29th November 2013) - Chan, Louis K. M.; Poole, Darren L.; Shen, Di; Healy, Mark P.; Donohoe, Timothy J.
Abstract The rhodium‐catalyzed methylation of ketones has been accomplished using methanol as the methylating agent and the hydrogen‐borrowing method. The sequence is notable for the relatively low temperatures that are required and for the ability of the reaction system to form α‐branched products with ease. Doubly alkylated ketones can be prepared from methyl ketones and two different alcohols by using a sequential one‐pot iridium‐ and rhodium‐catalyzed process.